Photocatalytic degradation of swine wastewater on aqueous TiO2 suspensions: optimization and modeling via Box-Behnken design. Issue 1 (January 2020) - Garcia, Bruno B.; Lourinho, G.; Romano, P.; Brito, P.S.D.
Abstract: Heterogeneous photocatalysis is a promising technology to treat many industrial wastewaters. To date, this potential has not been proven with wastewaters from agricultural origins, such as swine wastewater. In this work, the photocatalytic degradation of swine wastewater was studied by applying a response surface methodology based on the Box-Behnken design. The interactive effects of the variation of factors such as photocatalyst dosage (X1 ), wastewater concentration (X2 ), and irradiation time (X3 ) were analyzed to identify the optimal operating conditions for COD reduction. A second-order polynomial accurately represented organics degradation with a high adjusted R-squared (0.9666). The main effects of factor X2 and the quadratic effects of factors X2 and X3 were the most significant for COD reduction. The optimal conditions for COD degradation were 1.16 g L −1 for photocatalyst dosage, 1.68% for wastewater concentration, and irradiation time of 9.2 h. These results have been validated in a confirmation experiment and COD removal reached 91.7% (98.1 % predicted). Based on the Langmuir—Hinshelwood model, the reaction rate constant was 3.9×10 −3 min −1 . Besides, FTIR analysis indicated that Aeroxide® TiO2 reusability may be possible, especially for low wastewater concentrations. Heterogeneous photocatalysis can be applied as a technology for the integrated treatment of industrial wastewaters resulting from swine production. Abstract : Heterogeneous catalysis; Photocatalysis; Waste treatment; Wastewater management; Water treatment; Swine wastewater; Titanium dioxide; Optimization; Kinetics